SUE inspection: an effective method for systematic usability evaluation of hypermedia - Matera, M.; Costabile, M.F.; Garzotto, F.; Paolini, P. (IEEE transactions on systems, man and cybernetics. Part A, Systems and humans, 2002)
SUE inspection is a novel usability evaluation method for hypermedia, which falls into the category of inspection methods. Its primary goal is to favor a systematic usability evaluation (SUE), for supplying hypermedia usability inspectors with a structured flow of activities, allowing them to obtain more reliable, comparable, and cost-effective evaluation results. This is obtained especially due to the use of evaluation patterns, called abstract tasks (AT), which describe in details the activities that evaluators must carry out during inspection. AT helps share and transfer evaluation know-how among different evaluators, thus making it easier to learn the SUE inspection method by newcomers. A further notable advantage provided by the SUE inspection over other existent approaches is that it focuses on navigation and information structures, making evident some problems that other "surface-oriented" approaches might not reveal. This paper describes the SUE inspection for hypermedia. It also reports on a validation experiment, involving 28 evaluators, that has shown the major effectiveness and efficiency of the SUE inspection for hypermedia, with respect to traditional heuristic evaluation techniques.